Large‐Scale Synthesis of Nanostructured Carbon‐Ti4O7 Hollow Particles as Efficient Sulfur Host Materials for Multilayer Lithium‐Sulfur Pouch Cells. Issue 6 (23rd March 2022) - Mei, Shilin; Siebert, Andreas; Xu, Yaolin; Quan, Ting; Garcia‐Diez, Raul; Bär, Marcus; Härtel, Paul; Abendroth, Thomas; Dörfler, Susanne; Kaskel, Stefan; Lu, Yan
Abstract: Applications of advanced cathode materials with well‐designed chemical components and/or optimized nanostructures promoting the sulfur redox kinetics and suppressing the shuttle effect of polysulfides are highly valued. However, in the case of actual lithium‐sulfur (Li−S) batteries under practical working conditions, one long‐term obstacle still exists, which is mainly due to the difficulties in massive synthesis of such nanomaterials with low cost and ease of control on the nanostructure. Herein, we develop a facile synthesis of carbon coated Ti4 O7 hollow nanoparticles (C−Ti4 O7 ) using spherical polymer electrolyte brush as soft template, which is scalable via utilizing a minipilot reactor. The C−Ti4 O7 hollow nanoparticles provide strong chemical adsorption to polysulfides through the large polar surface and additional physical confinement by rich micro‐ & mesopores and have successfully been employed as an efficient sulfur host for multilayer pouch cells. Besides, the sluggish kinetics of the sulfur and lithium sulfide redox mechanism can be improved by the highly conductive Ti4 O7 via catalyzation of the conversion of polysulfides. Consequently, the C−Ti4 O7 based pouch cell endows a high discharge capacity of 1003 mAh g −1 at 0.05 C, a high‐capacity retention of 83.7 % after 100 cycles at 0.1 C, and a high Coulombic efficiency of 97.5 % at the 100th cycle. This work proposes an effective approach to transfer the synthesis of hollow Ti4 O7 nanoparticles from lab‐ to large‐scale production, paving the way to explore a wide range of advanced nanomaterials for multilayer Li−S pouch cells. Abstract : Polysulfides ball : A scalable synthesis of carbon coated Ti4 O7 hollow nanoparticles using spherical polymer electrolyte brush as soft template has been developed as efficient sulfur host for multilayer lithium‐sulfur pouch cells. The nanoparticles provide strong chemical adsorption to polysulfides and endow a stable cycling with a high‐capacity retention of 83.7 % after 100 cycles at 0.1 C.